1988
DOI: 10.1007/bf00976862
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting persistence of deaf college students

Abstract: Three of the maximum likelihood estimates in Figure 2, "Revised Model of Factors Affecting College Persistence with Maximum Likelihood Estimates," page 252, are incorrect. The value shown for the path between distance from home and participation in sponsored college activities is-. 1 3 , p<.05; the correct value is-. 0 1 , p>.10. The value shown in Figure 2 for the path between distance from home and persistence in college is-. 13, p<.05; the correct value is-. 0 8 , p >. 10. The interpretation of the correct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…including ''communication skills'' (see Barnhart 1991, Stinson & Walter 1992, 1995. The most elaborated and empirically most completed studies using the model in the context of hearingimpaired students and the decision-making process are those of Stinson, Scherer, and Walter (1987) and Walter (1992, 1995). These studies suggested that important factors for choosing higher education are that you know what you want (goal and commitment), have some experience in the mainstream (pre-entry attribute), are academically and social satisfied and integrated (institutional factors), and are doing well, while other studies emphasize the importance of communication skills.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…including ''communication skills'' (see Barnhart 1991, Stinson & Walter 1992, 1995. The most elaborated and empirically most completed studies using the model in the context of hearingimpaired students and the decision-making process are those of Stinson, Scherer, and Walter (1987) and Walter (1992, 1995). These studies suggested that important factors for choosing higher education are that you know what you want (goal and commitment), have some experience in the mainstream (pre-entry attribute), are academically and social satisfied and integrated (institutional factors), and are doing well, while other studies emphasize the importance of communication skills.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Students who engaged in more sponsored college activities were less likely to remain. Rather, it seemed that students who established relationships with roommates and those who developed independent living skills and time management skills felt more truly integrated into the college community [38].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been scholars who have investigated d/Deaf student persistence (Albertini, Kelly, & Matchett, 2011;Eilers-Crandall, 2009;Smith, 2004 There are few studies that focus on the persistence of d/Deaf college students (Boutin, 2008;Stinson, Scherer, & Walter, 1987). Similar to Black students, involvement in the academic and social systems of an institution, a connection with peers, specifically d/Deaf peers, confidence in their academic abilities, and access to information all play a role in d/Deaf students persisting and matriculating to graduation (Boutin, 2008;Stinson et al, 1987). Stinson et al (1987) (Getzel, 2008).…”
Section: The D/deaf Communitymentioning
confidence: 99%
“…Similar to Black students, involvement in the academic and social systems of an institution, a connection with peers, specifically d/Deaf peers, confidence in their academic abilities, and access to information all play a role in d/Deaf students persisting and matriculating to graduation (Boutin, 2008;Stinson et al, 1987). Stinson et al (1987) (Getzel, 2008). An environment does not evolve or exist prior to or separate from the people who create and use it (Razack, 2002).…”
Section: The D/deaf Communitymentioning
confidence: 99%
See 1 more Smart Citation